Method for controlling off-angle net-shaped cracks of high-carbon steel plate blank
By controlling the acid-soluble aluminum and nitrogen content in the molten steel and optimizing the continuous casting process parameters, the problem of off-angle network cracks in high-carbon steel slabs was solved, effectively reducing the incidence of cracks and improving the quality of rolled products.
Patent Information
- Application Number
- CN202411520390.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-29
AI Technical Summary
When producing high-carbon steel slabs, severe mesh cracks are easily generated on the upper and lower sides of the slabs or on the wide surface of the slabs, resulting in edge straight crack defects within the area 50mm away from the edge of the hot-rolled strip, affecting the rolled material Quality and increase cost.
By controlling the contents of acid-soluble aluminum (Als) and nitrogen (N) in the molten steel, ensure that [%Al]*[%N] ≤ 0.0002, and optimize the continuous casting process parameters, such as the physical and chemical indicators of the mold powder, the crystallizer Narrow surface taper, cooling water flow, drawing speed and superheat, etc., to improve the cooling uniformity of the slab and reduce the incidence of deviation angle network cracks.
Effectively reduced the occurrence rate of network cracks at the narrow surface deviation angle of high carbon steel slabs, the crack occurrence rate dropped from 100% to less than 1%, and the hot rolled plate edge straight crack incidence rate dropped from 100% to less than 5%, improving the rolling efficiency. It improves the surface quality of materials, reduces production costs, and improves user satisfaction.
Smart Images

Figure CN119328091A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of steel, and in particular relates to a method for controlling deviation angle mesh cracks in a high carbon steel slab. Background Art
[0002] Defect-free ingots are the ultimate goal pursued by continuous casting workers. In actual work, "defect-free" is a relative concept, which means that both the surface quality and internal quality of the continuous casting ingot must meet the requirements, and there are no defects on the surface of the continuous casting ingot that need to be cleaned, such as cracks, scars, and slag inclusions.
[0003] Among them, the surface cracks of continuous casting billets are the most common defects and the most difficult to control defects. According to the different morphologies of cracks, they can be divided into longitudinal cracks, transverse cracks, and mesh cracks; according to the location of the cracks, they can be divided into deviation angle longitudinal cracks, corner transverse cracks, deviation angle mesh cracks, etc. Among them, longitudinal cracks and transverse cracks are studied more, and the control measures are relatively mature. Deviation angle mesh cracks exist on most steel grades. They are generally mild and shallow in depth. They have little effect on the surface quality of rolled materials. Under normal circumstances, no measures are required. However, when producing high-carbon steel slabs, serious mesh cracks are prone to occur on the upper and lower sides of the narrow surface of the slab or the deviation angle position of the wide surface. The morphology of the cracks is generally longitudinal, the width of the crack area is about 20mm, the distance between the crack area and the corner is in the range of 10 to 50mm, the depth is generally about 5mm, and the deepest exceeds 10mm. This crack causes the hot-rolled strip to have an edge straight crack defect within 50mm of the edge, and the defect depth is within 1mm. It has a serious negative impact on the quality of hot-rolled products and causes huge cost losses.
[0004] Chinese patent CN 116751922 A discloses a method for reducing the occurrence of longitudinal cracks at the corners of a chamfered crystallizer in the production of high-carbon steel ingots. The method reduces the occurrence of longitudinal cracks at the corners of the chamfered crystallizer by strictly controlling the [S] content in the steel and the carbon content in the converter, optimizing the taper and strictly controlling the casting speed. The method mainly controls the incidence rate of longitudinal cracks at the corners of the chamfered crystallizer and has a good effect. However, the technology controls the incidence rate of longitudinal cracks at the corners of a special continuous casting crystallizer rather than the deviation angle mesh cracks.
[0005] Chinese patent CN 114505461 A discloses a method for improving corner cracks and middle cracks of slabs. The method achieves the improvement effect of reducing transverse cracks and middle cracks at the corners of the slabs by re-optimizing the temperature control interval at the corners of the slabs. However, the transverse cracks at the corners and the internal cracks (middle cracks) of the slabs that are mainly improved by this technology are not the same type of cracks as the angular mesh cracks. In addition, this technology only controls the corner temperature by setting two temperature control intervals to achieve the purpose of controlling corner cracks, and its control difficulty is very large.
[0006] Chinese patent CN 115889713 A discloses a continuous casting process for improving the quality of ultra-high carbon steel ingots. The process mainly optimizes the control of molten steel superheat and nitrogen content, protective slag performance, mold taper, secondary cooling process, slow cooling of ingots, etc., to improve the quality of high carbon steel ingots and improve the internal quality and surface quality of high carbon steel. However, the method is relatively general and the improvement effect on the deviation angle network crack is not clearly specified. Summary of the invention
[0007] In view of the problem of narrow surface deviation angle network cracks occurring when a slab continuous casting machine produces high carbon steel, the present invention provides a method for controlling deviation angle network cracks in a high carbon steel slab, thereby reducing the incidence of deviation angle network cracks in high carbon steel slabs with a carbon content of 0.55 to 0.80% from 100% to below 1%. The method is applicable to all slab continuous casting machines, and is particularly effective for wide and thick slab casting machines with a thickness greater than 150 mm and a length greater than 900 mm.
[0008] The technical solution adopted by the present invention is as follows:
[0009] A method for controlling deviation angle mesh cracks in a high carbon steel slab, comprising the following methods:
[0010] Control the content of Als and N in molten steel, [%Al]*[%N]≤0.0002, and when Als is between 0.020 and 0.035%, the N in the steel is controlled within 60ppm;
[0011] During continuous casting, a mold protection slag with the following physical and chemical indicators is used for protection casting: SiO2 29.0-32.0wt%, CaO 26.0-30.0wt%, Al2O3 4.0-5.0wt%, R2O 8-11wt%, F 8-10wt%, Fe2O3 0.4-0.6wt%, C 3.0-5.0wt%, melting point 1050-1100°C, viscosity 0.2-0.3Pa·S at 1300°C; wherein R2O represents any one or more of Na2O, K2O, and Li2O.
[0012] The taper of the narrow surface of the crystallizer is controlled between 1.08% and 1.15%;
[0013] The water cooling flow rate on the narrow side of the crystallizer is 430-450L / min; the water flow rate on the wide side is 4200-4500L / min;
[0014] The specific water volume of the continuous casting secondary cooling is 0.7-0.8L / kg, of which the water volume of the full roll section accounts for 12-15%, and the water flow density ratio of the wide and narrow sides is 0.9-1.0:1; the water flow density ratio is the water flow per unit area;
[0015] The continuous casting speed is controlled at 1.0-1.1 m / min. The low speed makes the shell of the ingot have enough thickness to withstand the static pressure of the internal molten steel when it leaves the crystallizer.
[0016] The mass percentage of C in the high carbon steel is 0.55-0.80%.
[0017] Furthermore, argon is used as the bottom blowing gas of the converter throughout the entire process; the frequency of re-blowing of the converter is reduced to less than 2 times.
[0018] The amount of LF slag is controlled at 12-15kg / t to ensure good submerged arc; the number of LF furnace heating times is ≤3 times / furnace, the furnace door is closed, and a slight positive pressure is maintained; during strong stirring, the bottom blowing flow rate is controlled at 600-800L / min, and the bright surface of the molten steel is ≤500mm; during weak stirring, the bottom blowing flow rate is controlled at 30-60L / min, and the bright surface of the molten steel is ≤50mm.
[0019] The nitrogen addition in the continuous casting process is controlled at ≤3ppm: the argon filling flow rate before the ladle pouring is ≥60m 3 / h, argon filling time is greater than 2min, oxygen content in the tundish before pouring is ≤0.5%; argon filling flow rate in the tundish during casting is ≥30m 3 / h, ensuring that the oxygen content in the middle bag is ≤0.5%.
[0020] During continuous casting, the shroud is sealed with argon gas, and the argon gas pressure is 0.2-0.4MPa, ensuring that the inside of the shroud is in a slightly positive pressure state during the casting process.
[0021] The thickness of the liquid slag layer of the crystallizer protective slag is 8 to 10 mm, and the slag consumption is 0.35 to 0.40 kg / t.
[0022] The arc alignment accuracy between the first pair of foot rollers and the copper tube on the narrow side of the crystallizer is ±0.05mm, the arc alignment accuracy between the second pair of foot rollers and the copper tube is -0.2mm, and the arc alignment accuracy between the third and fourth pairs of foot rollers and the copper tube is -0.3mm.
[0023] During continuous casting, the superheat of molten steel is 10-25℃.
[0024] The reason for the mesh cracks on the narrow surface of the slab deviation angle is that the crystallizer is cooled unevenly, resulting in deviation angle depressions. The austenite grains are coarse at the deviation angle depressions. During the secondary cooling process, the thermal stress and mechanical stress generated by the uneven cooling of the secondary cooling water and the poor arc alignment of the fan-shaped segment exceed the allowable strength of the steel grade, and finally cracks are generated at the deviation angle depressions. For aluminum-containing steel, the formation of aluminum nitride further deteriorates the strength of the austenite grain boundaries and increases the risk of cracks. In addition, low-melting-point substances such as Cu and As in the steel will also be enriched at the grain boundaries, further reducing the grain boundary strength and increasing the risk of cracks. Due to the high carbon content of high-carbon steel, the wide solid-liquid two-phase region, low tensile strength at high temperature, poor plasticity, and small solidification shrinkage of the initially generated blank shell, the blank shell and the crystallizer wall are in close contact under the static pressure of the molten steel. The blank shell is subject to large friction resistance during the casting process, which is more prone to cracks than low-carbon steel.
[0025] The method for controlling the deviation angle mesh cracks of high carbon steel slab provided by the present invention controls the product of acid-soluble aluminum and nitrogen in steel to ≤0.0002 and the nitrogen content in steel to ≤60ppm, redesigns the continuous casting secondary cooling parameters, controls the secondary cooling water volume to 0.7-0.8L / kg, re-optimizes the physical and chemical indicators of the protective slag, and solves the problem of uneven cooling of the slab in the crystallizer and the secondary cooling zone, and effectively improves the deviation angle mesh cracks of the slab produced by slab continuous casting of high carbon steel. The method of the present invention can greatly reduce the incidence of deviation angle mesh cracks on the narrow surface of the high carbon steel slab, and the crack incidence rate is reduced from 100% to less than 1%, and the incidence rate of straight cracks on the edge of the hot-rolled plate is reduced from 100% to less than 5%; it not only reduces the incidence rate of cracks in the slab, improves the yield rate of the hot-rolled plate, reduces the production cost, but also improves the surface quality of the rolled material, improves user satisfaction, and brings about an increase in the number of orders. At the same time, the method is convenient and simple to operate without increasing the labor intensity of the operator.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention controls the crack index of the ingot to be low by controlling the content of Als and N in the molten steel.
[0028] 2. The preferred physical and chemical indicators of the protective slag of the present invention are: SiO2 29.0-32.0wt%, CaO 26.0-30.0wt%, Al2O3 4.0-5.0wt%, R2O 8-11wt%, F 8-10wt%, Fe2O3 0.4-0.6wt%, C 3.0-5.0wt%, melting point 1050-1100℃, viscosity 0.2-0.3Pa·S at 1300℃, thickness of protective slag liquid slag layer 8-10mm, slag consumption 0.35-0.40kg / t, such protective slag has good fluidity and lubricity in the crystallizer, ensuring that the slag film between the inner wall of the crystallizer and the blank shell is mainly glassy slag film, so that the lubrication and heat transfer between the crystallizer wall and the solidified blank shell can be well controlled. However, due to the slow pulling speed of high carbon steel, the thermal conductivity of the protective slag cannot be too good, which is not conducive to the uniform growth of the blank shell. The protective slag provided by the present invention has moderate thermal conductivity and is conducive to the uniform growth of the blank shell.
[0029] 3. The present invention sets the taper of the narrow surface of the crystallizer to between 1.08% and 1.15% based on the solidification shrinkage characteristics of high carbon steel and the on-site working conditions. If the taper is too small, an air gap will be generated between the solidified billet shell and the crystallizer wall, resulting in coarse grains on the surface of the billet and an increased risk of the billet resisting cracks; if the taper is too large, the friction between the billet and the crystallizer will increase, which will also increase the risk of cracks.
[0030] 4. The crystallizer of the present invention adopts a strong cooling method to increase the thickness of the billet shell and improve the risk of crack resistance of the cast billet. The water cooling flow rate of the narrow surface of the crystallizer is 430-450L / min; the water flow rate of the wide surface is 4200-4500L / min
[0031] 5. In order to improve the cooling uniformity of the ingot, the secondary cooling of continuous casting adopts medium cooling intensity water, with a specific water volume of 0.7-0.8l / kg, of which the water volume in the full roll section accounts for 12-15%, and the water flow density ratio between the wide and narrow surfaces is 0.9-1.0.
[0032] 6. The method of the present invention can significantly reduce the incidence of angular mesh cracks on the narrow surface of high-carbon steel slabs, and the crack incidence rate is reduced from 100% to below 1%, and the incidence rate of straight cracks on the edge of hot-rolled plates is reduced from 100% to below 5%. It not only reduces the crack incidence rate of the ingot, improves the yield rate of the hot-rolled plate, and reduces the production cost, but also improves the surface quality of the rolled material, improves user satisfaction, and brings about an increase in the number of orders. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a photo of a narrow surface deviation angle mesh crack on a continuous casting billet;
[0034] Figure 2 This is a photograph of the continuous casting slab produced in Example 1. DETAILED DESCRIPTION
[0035] The present invention provides a method for controlling deviation angle network cracks in a high carbon steel slab with a carbon mass percentage of 0.55 to 0.80%, which is specifically as follows:
[0036] 1) Control of [N] in molten steel: For aluminum-containing steel, the influence of [Als] and [N] in steel on network cracks is mainly through the precipitation of AlN at the austenite grain boundary, which reduces the grain boundary strength and causes cracks. For narrow surface network cracks of slab deviation angle, when [%Al]*[%N]≤0.0002, the crack index of the ingot is low; when [Als] is between 0.020 and 0.035%, the [N] in the steel is controlled within 60ppm, and the crack index of the ingot is low.
[0037] 2) The nitrogen control plan is as follows: ① Argon is used throughout the bottom blowing process of the converter; ② The number of re-blowing times of the converter is reduced, and the number of re-blowing times is ≯2 times; ③ The first re-blowing furnace does not smelt high-carbon steel; ④ The amount of LF slag is controlled at 12-15kg / t to ensure good arc burial; ⑤ The number of LF furnace heating times is ≤3 times / furnace, and the furnace door is closed to maintain a slight positive pressure; ⑥ During strong stirring, the bottom blowing flow rate is controlled at 600-800L / min, and the bright surface of the molten steel is ≤500mm; ⑦ During weak stirring, the bottom blowing flow rate is controlled at 30-60L / min, and the slag surface of the molten steel fluctuates slightly, and the bright surface of the molten steel is ≤50mm; ⑧ The nitrogen increase in the continuous casting process is controlled at ≤3ppm: the argon filling flow rate before the ladle is poured is ≥60m 3 / h, argon filling time is greater than 2min, oxygen content in the tundish before pouring is ≤0.5%; argon filling flow rate in the tundish during casting is ≥30m 3 / h, ensuring that the oxygen content in the tundish is ≤0.5%; the long nozzle is sealed with argon gas, and the argon gas pressure is 0.2-0.4MPa, ensuring that the inside of the long nozzle is in a slightly positive pressure state during the casting process.
[0038] 3) Crystallizer protection slag: The physical and chemical indicators of the protection slag are SiO2: 29.0~32.0wt%, CaO: 26.0~30.0wt%, Al2O3: 4.0~5.0wt%, R2O: 8~11wt%, F: 8~10wt%, Fe2O3: 0.4~0.6wt%, C: 3.0~5.0wt%, melting point is 1050~1100℃, viscosity is 0.2~0.3Pa·S (at 1300℃), thickness of the protection slag liquid slag layer is 8~10mm, and the slag consumption is 0.35~0.40kg / t.
[0039] 4) Crystallizer taper: The taper of the narrow surface of the crystallizer is set between 1.08% and 1.15%.
[0040] 5) Crystallizer cooling water: The water cooling flow rate on the narrow side of the crystallizer is 430-450 L / min; the water flow rate on the wide side is 4200-4500 L / min.
[0041] 6) Secondary cooling water: The specific water volume of continuous casting secondary cooling is 0.7-0.8L / kg, of which the water volume in the full roll section accounts for 12-15%, and the water flow density ratio between the wide and narrow sides is 0.9-1.0.
[0042] 7) Pulling speed: The pulling speed is controlled at 1.0~1.1m / min.
[0043] 8) Molten steel superheat: 10~25℃.
[0044] 9) Crystallizer arc alignment: The arc alignment accuracy of the first pair of foot rollers and the copper tube on the narrow side of the crystallizer is ±0.05mm, the arc alignment accuracy of the second pair of foot rollers and the copper tube is -0.2mm, and the arc alignment accuracy of the third and fourth pairs of foot rollers and the copper tube are both -0.3mm.
[0045] The present invention is described in detail below with reference to the embodiments.
[0046] Example 1
[0047] One furnace of high carbon steel 65Mn was cast on a slab continuous casting machine with a cross section of 230mm×1600mm. Process control parameters:
[0048] 1) The [Als] and [N] contents in the steel are 0.025% and 55 ppm respectively, [%Al]*[%N]=0.00014≤0.0002, meeting the requirements.
[0049] 2) Nitrogen control scheme: ① Argon is used throughout the bottom blowing process of the converter; ② The converter is reblown once; ③ The first furnace without reblowing; ④ The LF slag volume is controlled at 14kg / t, and the arc is well buried; ⑤ The LF furnace is heated up 3 times, the furnace door is closed, and a slight positive pressure is maintained; ⑥ When strong stirring, the bottom blowing flow rate is 730L / min; ⑦ When weak stirring, the bottom blowing flow rate is controlled at 32L / min; ⑧ The nitrogen increase in the continuous casting process is 0.5ppm: the argon filling flow rate before the ladle is poured is 110m 3 / h, argon filling time is greater than 2.20min, oxygen content in the tundish before pouring is ≤0.3%; argon filling flow rate in the tundish during casting is ≥40m 3 / h, the oxygen content in the tundish is 0.4%; the argon pressure at the long water outlet is 0.25MPa.
[0050] 3) Crystallizer protection slag: The physical and chemical indicators of the protection slag are SiO2: 30.3wt%, CaO: 29.0wt%, Al2O3: 4.3wt%, R2O: 8.5wt%, F: 9.2wt%, Fe2O3: 0.45wt%, C: 3.9wt%, melting point is 1073℃, viscosity is 0.28Pa·S at 1300℃, thickness of the protection slag liquid slag layer is 9mm, and the slag consumption is 0.38kg / t.
[0051] 4) Crystallizer taper: Narrow surface taper 1.13%.
[0052] 5) Crystallizer cooling water flow: narrow side: 445L / min; wide side: 4350L / min.
[0053] 6) Secondary cooling water: The specific water volume is 0.74L / kg, of which the water volume in the foot roll section accounts for 13.5%, and the water flow density ratio between the wide and narrow surfaces is 0.94.
[0054] 7) Pulling speed: 1.08m / min.
[0055] 8) Molten steel superheat: between 15 and 25°C.
[0056] 9) Crystallizer arc alignment: The arc alignment accuracy between the first pair of narrow side foot rollers and the copper tube is 0.0mm, the arc alignment accuracy between the second pair of narrow side foot rollers and the copper tube is -0.2mm, and the arc alignment accuracy between the third / fourth pair of narrow side foot rollers and the copper tube is -0.3mm.
[0057] Example 2
[0058] One furnace of high carbon steel 75Cr1 was cast on a slab continuous casting machine with a cross section of 230mm×2200mm. Process control parameters:
[0059] 1) The [Als] and [N] contents in the steel are 0.024% and 53 ppm respectively, [%Al]*[%N]=0.00013≤0.0002, meeting the requirements.
[0060] 2) Nitrogen control scheme: ① Argon is used throughout the bottom blowing process of the converter; ② The converter is reblown twice; ③ The first furnace without reblowing; ④ The LF slag volume is controlled at 13.2kg / t, and the arc is well buried; ⑤ The LF furnace is heated up three times, the furnace door is closed, and a slight positive pressure is maintained; ⑥ When strong stirring, the bottom blowing flow rate is 680L / min; ⑦ When weak stirring, the bottom blowing flow rate is controlled at 45L / min; ⑧ The nitrogen increase in the continuous casting process is 1.5ppm: the argon filling flow rate before the ladle pouring is 100m 3 / h, argon filling time is greater than 2.30min, oxygen content in the tundish before pouring is ≤0.4%; argon filling flow rate in the tundish during casting is ≥35m 3 / h, the oxygen content in the tundish is 0.3%; the argon pressure at the long water outlet is 0.3MPa.
[0061] 3) Crystallizer protection slag: The physical and chemical indicators of the protection slag are SiO2: 30.5wt%, CaO: 28.0wt%, Al2O3: 4.5wt%, R2O: 9.0wt%, F: 9.0wt%, Fe2O3: 0.5wt%, C: 3.5wt%, melting point is 1068℃, viscosity is 0.25Pa·S at 1300℃, thickness of the protection slag liquid slag layer is 10mm, and the slag consumption is 0.39kg / t.
[0062] 4) Crystallizer taper: Narrow surface taper 1.14%.
[0063] 5) Crystallizer cooling water flow: narrow side: 442L / min; wide side: 4450L / min.
[0064] 6) Secondary cooling water: The specific water volume is 0.75L / kg, of which the water volume in the foot roll section accounts for 13%, and the water flow density ratio between the wide and narrow surfaces is 0.96.
[0065] 7) Pulling speed: 1.1m / min.
[0066] 8) Molten steel superheat: between 15 and 25°C.
[0067] 9) Crystallizer arc alignment: The arc alignment accuracy between the first pair of narrow side foot rollers and the copper tube is 0.0mm, the arc alignment accuracy between the second pair of narrow side foot rollers and the copper tube is -0.2mm, and the arc alignment accuracy between the third / fourth pair of narrow side foot rollers and the copper tube is -0.3mm.
[0068] Comparative Example 1
[0069] One furnace of high carbon steel 75Cr1 was cast on a slab continuous casting machine with a cross section of 230mm×2200mm. Process control parameters:
[0070] 1) The [Als] and [N] contents in the steel are 0.035% and 58 ppm respectively.
[0071] 2) Nitrogen control scheme: ① Argon is used throughout the bottom blowing process of the converter; ② The converter is reblown twice; ③ The first furnace without reblowing; ④ The LF slag volume is controlled at 13.2kg / t, and the arc is well buried; ⑤ The LF furnace is heated up three times, the furnace door is closed, and a slight positive pressure is maintained; ⑥ When strong stirring, the bottom blowing flow rate is 680L / min; ⑦ When weak stirring, the bottom blowing flow rate is controlled at 45L / min; ⑧ The nitrogen increase in the continuous casting process is 1.5ppm: the argon filling flow rate before the ladle pouring is 100m 3 / h, argon filling time is greater than 2.30min, oxygen content in the tundish before pouring is ≤0.4%; argon filling flow rate in the tundish during casting is ≥35m 3 / h, the oxygen content in the tundish is 0.3%; the argon pressure at the long water outlet is 0.3MPa.
[0072] 3) Crystallizer protection slag: The physical and chemical indicators of the protection slag are SiO2: 30.5wt%, CaO: 28.0wt%, Al2O3: 4.5wt%, R2O: 9.0wt%, F: 9.0wt%, Fe2O3: 0.5wt%, C: 3.5wt%, melting point is 1068℃, viscosity is 0.25Pa·S at 1300℃, thickness of the protection slag liquid slag layer is 10mm, and the slag consumption is 0.39kg / t.
[0073] 4) Crystallizer taper: narrow surface taper 1.15%.
[0074] 5) Crystallizer cooling water flow: narrow side: 442L / min; wide side: 4450L / min.
[0075] 6) Secondary cooling water: The specific water volume is 0.73L / kg, of which the water volume in the foot roll section accounts for 13%, and the water flow density ratio between the wide and narrow surfaces is 0.85.
[0076] 7) Pulling speed: 1.06m / min.
[0077] 8) Molten steel superheat: between 15 and 25°C.
[0078] 9) Crystallizer arc alignment: The arc alignment accuracy between the first pair of narrow side foot rollers and the copper tube is 0.0mm, the arc alignment accuracy between the second pair of narrow side foot rollers and the copper tube is -0.2mm, and the arc alignment accuracy between the third / fourth pair of narrow side foot rollers and the copper tube is -0.3mm.
[0079] Comparative Example 2
[0080] One furnace of high carbon steel 65Mn was cast on a slab continuous casting machine with a cross section of 230mm×1800mm. Process control parameters:
[0081] 1) The [Als] and [N] contents in the steel are 0.035% and 50 ppm respectively.
[0082] 2) Nitrogen control scheme: ① Argon is used throughout the bottom blowing process of the converter; ② The converter is reblown twice; ③ The first furnace without reblowing; ④ The LF slag volume is controlled at 13.2kg / t, and the arc is well buried; ⑤ The LF furnace is heated up three times, the furnace door is closed, and a slight positive pressure is maintained; ⑥ When strong stirring, the bottom blowing flow rate is 680L / min; ⑦ When weak stirring, the bottom blowing flow rate is controlled at 45L / min; ⑧ The nitrogen increase in the continuous casting process is 1.5ppm: the argon filling flow rate before the ladle pouring is 100m 3 / h, argon filling time is greater than 2.30min, oxygen content in the tundish before pouring is ≤0.4%; argon filling flow rate in the tundish during casting is ≥35m 3 / h, the oxygen content in the tundish is 0.3%; the argon pressure at the long water outlet is 0.3MPa.
[0083] 3) Crystallizer protection slag: The physical and chemical indicators of the protection slag used in this test are SiO2: 30.5wt%, CaO: 28.0wt%, Al2O3: 4.5wt%, R2O: 9.0wt%, F: 9.0wt%, Fe2O3: 0.5wt%, C: 3.5wt%, melting point is 1068℃, viscosity is 0.25Pa·S at 1300℃, thickness of the protection slag liquid slag layer is 10mm, and slag consumption is 0.39kg / t.
[0084] 4) Crystallizer taper: Narrow surface taper 1.05%.
[0085] 5) Crystallizer cooling water flow: narrow side: 442L / min; wide side: 4450L / min.
[0086] 6) Secondary cooling water: The specific water volume is 0.75L / kg, of which the water volume in the foot roll section accounts for 13%, and the water flow density ratio between the wide and narrow surfaces is 0.96.
[0087] 7) Pulling speed: 1.05m / min.
[0088] 8) Molten steel superheat: between 15 and 25°C.
[0089] 9) Crystallizer arc alignment: The arc alignment accuracy between the first pair of narrow side foot rollers and the copper tube is 0.2mm, the arc alignment accuracy between the second pair of narrow side foot rollers and the copper tube is -0.2mm, and the arc alignment accuracy between the third / fourth pair of narrow side foot rollers and the copper tube is -0.3mm.
[0090] The implementation effects of the above embodiments and comparative examples are shown in Table 1.
[0091] Table 1
[0092] Narrow surface deviation angle network crack incidence rate % Hot rolling edge crack incidence % Example 1 0 2 Example 2 0 1.5 Comparative Example 1 55 79.2 Comparative Example 2 69.2 85.3
[0093] The above-mentioned detailed description of a method for controlling deviation angle network cracks in a high carbon steel slab with reference to the embodiment is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for controlling deviation angle network cracks in high carbon steel slabs, characterized in that: The following methods are included: Control the content of Als and N in molten steel, [%Al]*[%N]≤0.0002, and when Als is between 0.020 and 0.035%, the N in the steel is controlled within 60ppm; During continuous casting, a mold protection slag with the following physical and chemical indicators is used for protection casting: SiO2 29.0-32.0wt%, CaO2 6.0-30.0wt%, Al2O3 4.0-5.0wt%, R2O 8-11wt%, F 8-10wt%, Fe2O3 0.4-0.6wt%, C 3.0-5.0wt%, melting point 1050-1100°C, viscosity 0.2-0.3Pa·S at 1300°C; The taper of the narrow surface of the crystallizer is controlled between 1.08% and 1.15%; The water cooling flow rate on the narrow side of the crystallizer is 430-450L / min; the water flow rate on the wide side is 4200-4500L / min; The specific water volume of the continuous casting secondary cooling is 0.7-0.8L / kg, of which the water volume of the foot roll section accounts for 12-15%, and the water flow density ratio of the wide side and the narrow side is 0.9-1.0:1; The continuous casting speed is controlled at 1.0-1.1 m / min; The mass percentage of C in the high carbon steel is 0.55-0.80%.
2. The method for controlling deviation angle network cracks in high carbon steel slab according to claim 1, characterized in that: Argon is used as the bottom blowing gas of the converter throughout the whole process; the frequency of re-blowing of the converter is reduced to less than 2 times.
3. The method for controlling deviation angle network cracks in high carbon steel slab according to claim 1, characterized in that: The amount of LF slag is controlled at 12-15kg / t; the number of LF furnace heating times is ≤3 times / furnace, and the furnace door is closed; during strong stirring, the bottom blowing flow rate is controlled at 600-800L / min, and the bright surface of the molten steel is ≤500mm; during weak stirring, the bottom blowing flow rate is controlled at 30-60L / min, and the bright surface of the molten steel is ≤50mm.
4. The method for controlling deviation angle network cracks in high carbon steel slab according to claim 1, characterized in that: The nitrogen addition in the continuous casting process is controlled at ≤3ppm: the argon filling flow rate before the ladle pouring is ≥60m 3 / h, argon filling time is greater than 2min, oxygen content in the tundish before pouring is ≤0.5%; argon filling flow rate in the tundish during casting is ≥30m 3 / h, ensuring that the oxygen content in the middle bag is ≤0.5%.
5. The method for controlling deviation angle network cracks in high carbon steel slab according to claim 1, characterized in that: During continuous casting, the long nozzle is sealed with argon gas, and the argon gas pressure is 0.2~0.4MPa.
6. The method for controlling deviation angle network cracks in high carbon steel slab according to claim 1, characterized in that: The thickness of the liquid slag layer of the crystallizer protective slag is 8 to 10 mm, and the slag consumption is 0.35 to 0.40 kg / t.
7. The method for controlling deviation angle network cracks in high carbon steel slab according to claim 1, characterized in that: The arc alignment accuracy between the first pair of foot rollers and the copper tube on the narrow side of the crystallizer is ±0.05mm, the arc alignment accuracy between the second pair of foot rollers and the copper tube is -0.2mm, and the arc alignment accuracy between the third and fourth pairs of foot rollers and the copper tube is -0.3mm.
8. The method for controlling deviation angle network cracks in high carbon steel slab according to claim 1, characterized in that: During continuous casting, the superheat of molten steel is 10-25℃.
9. The method for controlling deviation angle network cracks in high carbon steel slab according to claim 1, characterized in that: The occurrence rate of the off-angle network cracks in the high carbon steel slab is less than 1%.
Citation Information
Patent Citations
Method for improving corner cracks and middle cracks of plate blank
CN114505461A
Continuous casting process for improving quality of ultra-high carbon steel casting blank
CN115889713A
Method for reducing corner longitudinal cracks generated during production of high-carbon steel casting blank by chamfering crystallizer
CN116751922A
Continuous casting mould fluxes and preparation method thereof
CN101468387A
Production method for intermediate carbon intermediate silicon high aluminum dual-phase steel continuous casting
CN112795834A
Cited By
Method for controlling corner transverse cracks of ultra-high carbon steel casting blank
CN119839260A